2011
DOI: 10.1093/jpepsy/jsr044
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Interventions for Sleep Problems in Children With Autism Spectrum Disorders: Current Findings and Future Directions

Abstract: Although more rigorous research is required in order for any sleep interventions for children with ASD to be considered probably efficacious or well-established, the current literature should be used to guide clinical decisions and direct research questions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
113
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(113 citation statements)
references
References 50 publications
0
113
0
Order By: Relevance
“…Given that behavioral insomnia of childhood and inadequate sleep hygiene were commonly diagnosed sleep disorders, treatments that emphasize parent sleep education either alone or in combination with medications appear to be warranted. 22,23 These behavioral treatments, including those emphasizing a calming bedtime routine and soothing sleep environment, are also effective for other forms of insomnia, including those related to core deficits of ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Given that behavioral insomnia of childhood and inadequate sleep hygiene were commonly diagnosed sleep disorders, treatments that emphasize parent sleep education either alone or in combination with medications appear to be warranted. 22,23 These behavioral treatments, including those emphasizing a calming bedtime routine and soothing sleep environment, are also effective for other forms of insomnia, including those related to core deficits of ASD.…”
Section: Discussionmentioning
confidence: 99%
“…84 Regardless of the etiology, children with ASD with poor quality sleep have higher rates of internalizing and externalizing behavioral disorders and lower levels of adaptive functioning, 85 although recent preliminary studies suggest that several treatment modalities, such as behavioral interventions and melatonin, can improve sleep quality and improve daytime functioning of children with ASD and reduce caregiver stress. 86,87 Pediatricians and parents of children with ASD agree that improvement in addressing sleep problems in the primary care setting is needed. 4 An expert panel developed practice pathway for the evaluation and treatment of sleep problems in children with ASD can provide guidance to PCCs.…”
Section: What Is Known About Medical Conditions Associated With Asd?mentioning
confidence: 99%
“…The effectiveness of selective serotonin reuptake inhibitors (SSRIs) for repetitive behaviours has been questioned: the largest clinical trial for ASD found no effect of citalopram, and its use was associated with adverse effects. 70 Risperidone and aripiprazole significantly reduced repetitive behaviours in children with ASD, 75 83 and which require medical intervention (see recent guideline 74 ).…”
Section: Hyperactivity and Inattentionmentioning
confidence: 99%